Cuidados no fim da vida de pessoas idosas institucionalizadas : contradições e desafios - Clos, Michelle Bertóglio (2016)
This is a study of descriptive and qualitative approach whose overall goal is to understand how care is being implemented at the end of life in Long Staying Institutions for the Aged in the metropolitan region of Porto Alegre. Six institutions in 6 municipalities in the metropolitan region, including the capital, were selected. We interviewed 19 subjects comprised of staff and responsible 13 / family for institutionalized elderly, summing up a total of 32 subjects. In this sense, we sought to investigate whether ILPI are structured to recognize the needs of care to ensure comfort and dignity in the dying process of their patients. The central categories of this study were outlined as: care, integrity, individuality, relationships and spirituality. From the analysis of the content of interviews and field observations, it can be said that there is insecurity in these host structures and ignorance of the philosophy of hospice care and end of life. Because there is weakness in the effectiveness of care, there is compensation for the structural difficulties with speech affection for the technical team. Also it is identified a relationship between care quality and availability of financial resources, demonstrating an indicative reification of care, or care as a commodity to be sold.